ESTIMATION FOR BOUNDED SOLUTIONS OF INTEGRAL INEQUALITIES SOME NEW NON-LINEAR RETARDER INTEGRO-DIFFERENTIAL INEQUALITIES. (Journal of Sciences & Technology, 2019)
In this paper, we establish some new non-linear retarded  integro-differential inequalities in tow and n independent variables.